Tale of two countries: Emissions scenarios for China and India - Emanuele Massetti (Fondazione Eni Enrico Mattei (FEEM), 2011)
The aim of the paper is to present evidence that China and India are, and will remain, two very different actors in international negotiations to control global warming. We base our conclusions on historical data and on scenarios until 2050. The Business-as-Usual scenario (BaU) is compared to four Emissions Tax scenarios to draw insights on major transformations in energy use and in energy supply and to assess the possible contribution of China and India to a future international climate architecture. We study whether or not the Copenhagen intensity targets require more action than the BaU scenario and we assess whether the emissions reductions induced by the four tax scenarios are compatible with the G8 and MEF pledge to reduce global emissions by 50% in 2050.
Keywords: Q32; Q43; Q54; Q43; O53; P52; 330; Climate Change; China; India; Energy Efficiency; Energy and Development